A randomised, controlled, feasibility trial of an online, self-guided breathlessness supportive intervention (SELF-BREATHE) for individuals with chronic breathlessness due to advanced disease - Charles C. Reilly; Matthew Maddocks; Trudie Chalder; Katherine Bristowe; Irene J. Higginson (ERJ Open Research, 2023)
Introduction SELF-BREATHE is a complex, transdiagnostic, supportive, digital breathlessness intervention co-developed with patients. SELF-BREATHE seeks to build capacity and resilience within health services by improving the lives of people with chronic breathlessness using nonpharmacological, self-management approaches. This study aimed to determine whether SELF-BREATHE is feasible to deliver and acceptable to patients living with chronic breathlessness. Methods A parallel, two-arm, single-blind, single-centre, randomised controlled, mixed-methods feasibility trial with participants allocated to 1) intervention group (SELF-BREATHE) or 2) control group (usual National Health Service (NHS) care). The setting was a large multisite NHS foundation trust in south-east London, UK. The participants were patients living with chronic breathlessness due to advanced malignant or nonmalignant disease(s). Participants were randomly allocated (1:1) to an online, self-guided, breathlessness supportive intervention (SELF-BREATHE) and usual care or usual care alone, over 6 weeks. The a priori progression criteria were ≥30% of eligible patients given an information sheet consented to participate; ≥60% of participants logged on and accessed SELF-BREATHE within 2 weeks; and ≥70% of patients reported the methodology and intervention as acceptable. Results Between January 2021 and January 2022, 52 (47%) out of 110 eligible patients consented and were randomised. Of those randomised to SELF-BREATHE, 19 (73%) out of 26 logged on and used SELF-BREATHE for a mean±sd (range) 9±8 (1–33) times over 6 weeks. 36 (70%) of the 52 randomised participants completed and returned the end-of-study postal questionnaires. SELF-BREATHE users reported it to be acceptable. Post-intervention qualitative interviews demonstrated that SELF-BREATHE was acceptable and valued by users, improving breathlessness during daily life and at points of breathlessness crisis. Conclusion These data support the feasibility of moving to a fully powered, randomised controlled efficacy trial with minor modifications to minimise missing data (i.e. multiple methods of data collection: face-to-face, telephone, video assessment and by post).